MODEL ОF CONSUMER BEHAVIOR TRANSFORMATION AS A BASIS FOR MARKETING STRATEGY - V.Savelyev (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article concerns with the basic consumer segments. The consumer needs are analyzed in the article and the model of change in consumer behavior is created. The article proposes the recommendations on effective strategic actions in order to competitive capacity increase. It is determined that in low purchasing power conditions, focus on meeting the needs of loyal customer segments will allow companies to increase the competitiveness of the market supply. Adaptation of marketing strategy in low purchasing power conditions is a creative process in which success is based on the orientation of the changed consumption motives.